Buddhism and the transformation of old age in medieval Japan - Drott, Edward Robertson (University of Hawaiʻi Press, 2016)
This title charts the shifting sets of meanings ascribed to old age in medieval Japan, tracing the processes by which the aged body was transformed into a symbol of otherworldly power and the cultural, political, and religious circumstances that inspired its reimagination. Edward R. Drott examines how the aged body was used to conceptualise forms of difference and to convey religious meanings in a variety of texts.